THE USE OF STUDENTS TEAMS ACHIEVEMENT DIVISIONS (STAD) TECHNIQUE IN TEACHING WRITING RECOUNT TEXT (ELang | An English Language Education Journal, 2019)
This research paper entitled “The Use of Students Teams Achievement Divisions (STAD) Technique in Teaching Writing Recount Text” is intended to find out the effectiveness of STAD technique to improve students writing skill and to investigate the significant of STAD technique comparing to conventional method. The research design in this study was a quasi experimental research that consisted of pre-test and post-test as the treatment. This study took the second grade students of SMP Negeri 04 Pangalengan 2019/2020 academic year that involved 40 students of experimental group and 40 students of control group. After conducting the research and computing the data, the writer concludes that STAD technique is effective in teaching writing recount text. It can be seen from the result of t-observed value. Before the treatments, the t-observed is less than t-table (0.6 < 2.000) the null hypothesis is retained. It means there is no significant difference in writing ability between experimental group and control group before treatments. After the treatment, the t-observed is bigger than t-table (3.92 > 2.000) and the alternative hypothesis is accepted. It means there is significance different in the result between experimental group and control group in teaching writing recount text by using STAD technique. This also means that STAD technique is effective in teaching writing recount text to the second grade of Junior High School. From the result of the questionnaire, the writer can conclude that almost all of students like writing, they agree that the use of STAD can be more active, communicative, makes students understand the material better and can improve they ability to work individually or in groups especially in writing recount text. In other words, students get positive responses in teaching writing by using STAD for the second grade of junior high school.Key Words: Students Teams Achievement Divisions (STAD), Recount Text